Contribution of Transient Receptor Potential Ankyrin 1 to Chronic Pain in Aged Mice With Complete Freund's Adjuvant–Induced Arthritis. Issue 9 (September 2014) - Garrison, Sheldon R.; Stucky, Cheryl L.
<x xml:space="preserve">Abstract</x> Objective To investigate age‐related differences in mechanical sensitivity to inflammatory pain and determine the contribution of transient receptor potential ankyrin 1 (TRPA1) to mechanical hypersensitivity during chronic inflammation in young and aged mice with complete Freund's adjuvant (CFA)–induced arthritis. Methods Mechanical sensitivity in young (3‐month‐old) and aged (24‐month‐old) wild‐type (TRPA1+/+) mice and TRPA1‐deficient (TRPA1−/−) mice was measured behaviorally for 8 weeks following injection of CFA into the plantar hind paw. The severity of inflammation was evaluated by histologic analyses and hind‐paw measurements. Ex vivo preparations of the skin saphenous nerve from mice were assessed for C‐fiber sensitivity. Results Among naive (uninjured) wild‐type mice, aged animals were less sensitive than young animals to mechanical stimuli. Afferent recordings of C‐fibers from TRPA1−/− mice indicated that TRPA1 contributes to the normal mechanical sensitivity in both age groups. Following injection of CFA, both young and aged TRPA1+/+ mice exhibited mechanical hypersensitivity. In young TRPA1−/− mice injected with CFA, peak development of mechanical hypersensitivity was delayed until week 4, when they exhibited a sharp decrease (9‐fold) in the mechanical paw withdrawal threshold, whereas aged TRPA1−/− mice did not exhibit mechanical hypersensitivity at any time during the 8 weeks after CFA injection. Recordings of C‐fibers from the saphenous nerve supported these findings, with results indicating that both young and aged TRPA1+/+ mice exhibited increased action potential firing at 8 weeks after CFA injection (increases of 25% and 60%, respectively). Interestingly, among TRPA1−/− mice injected with CFA, mechanical firing was increased markedly in the C‐fibers of young mice (increase of 80%) but not in the C‐fibers of aged mice. Conclusion These findings reveal marked differences in the long‐term mechanical behavioral sensitivity of aged and young mice, and suggest that TRPA1 may be a key contributor to the transition from acute to chronic inflammatory pain in response to mechanical stimuli as well as to the development of nociceptor sensitization selectively in aged mice.